Evaluating a treatment without extinction for elopement maintained by access to stereotypy. Issue 3 (27th January 2020) - Boyle, Megan A.; Bacon, McKenzie T.; Brewer, Emily M.; Carton, Samantha M.; Gaskill, Lauren A.
Abstract : Elopement is a common and potentially dangerous form of problem behavior. Results of a functional analysis found that the elopement of a child with autism was maintained by access to stereotypy in the form of door play. We implemented functional communication training and contingency‐based delays dependent on the absence of elopement and increased the amount of time the participant waited prior to engaging in stereotypy. We also conducted treatment‐extension probes, with the participant waiting up to 10 min without elopement.